Goat – for Nutritional and Livelihood Security in Bundelkhand Region - Singh, M K; Dixit, A K; Kumar, N; Ramachandran, N; Singh, S K; Singh, S V; Roy, A K; Yadav, J S; Singh, A K; Singh, R; Singh, P (Indian Farming, 2015)
Goat farming with improved package of practices and critical inputs has immense potential for sustainable nutrition and livelihood in Bundelkhand. Poor need realization and adoption of critically important inputs due to knowledge gap is major constraints therefore, Capacity building of goat keeper is essential for increased adoption of critical management practices and inputs (supplementary feeding, use of high potential buck and breeding practices, prophylactic health measures and proper housing) for realizing more profit from goats. Improvement of waste lands may be developed as perennial silvipastures. Extensive (zero-input) system of goat rearing should be gradually replaced with strategic and semi-intensive feeding systems.